The cosmic mystery tour : a high-speed journey through space & time - Mee, Nicholas (Oxford : Oxford University Press, 2019)
This is a lively, inspiring beginner's guide to how the universe works. This book contains bite-sized chapters present the discoveries of modern physics, astronomy, and cosmology. It also has background stories of the research and researchers bring the science to life.
Part I: The laws of the cosmos. The path to immortality -- The Rosetta Stone and quantum waves -- We're having a field day! -- Cosmic ripples -- Lovely LISA -- Animated atom boy -- Twinkle, twinkle little star -- Forces of the world unite! -- Most of the universe is missing! -- Part II: The history, geography and architecture of the cosmos. From Genesis to Revelation -- The battle for the cosmos! -- Alchemical furnaces of the cosmos -- Diamonds in the sky! -- From the Leviathan to the Behemoth -- The crab and the jellyfish -- The ultimate heavy metal space rock -- Pan galactic gargle blaster -- Cosmic spacequakes -- Doctor atomic and the black hole -- Supcrmassive black holes -- Part III: The biology of the cosmos. The Gorgon's head! -- Raise your glasses to the skies! -- Life, but not as we know it! -- To boldly go... -- Somewhere over the rainbow -- Where is everybody?.
Includes bibliographical references and index.
Keywords: Cosmology -- Popular works; Physics -- Popular works